Victims or intruders? Refugee portrayals in the news in Turkey, Bulgaria and the UK. (September 2021) - Ozdora-Aksak, Emel; Connolly-Ahern, Colleen; Dimitrova, Daniela
News shapes audiences' views of people and events beyond their immediate physical environment. Since the mass migration of refugees from Syria represents one of the worst humanitarian crises in modern history, its news coverage necessarily shaped the way global audiences understood the crisis. This qualitative study employs critical discourse analysis (CDA), specifically Van Leeuwen's Discourse and Practice: New Tools for Critical Discourse Analysis (2008) as a social practice approach, to reveal and compare the discursive strategies used in the print media coverage of the Syrian refugees in three European countries: Turkey, Bulgaria and the UK. The findings show significant differences in the discourse used to describe the refugees and different approaches in terms of contextualization, spaces and actions depicted in the media coverage in each country. The study reveals the ongoing dialogue between journalistic practice and political decision making in three countries impacted to varying extents by the ongoing crisis.